Developing a deprivation index to study geographical health inequalities in Ecuador - Andrés Peralta; Verónica Espinel-Flores; Mercè Gotsens; Glòria Pérez; Joan Benach; Marc Marí-Dell'Olmo (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVES: To develop a deprivation index to study health inequalities in 221 areas of Ecuador, to describe the pattern of deprivation in Ecuador, and to explore the applications of the index to study health inequalities by analysing the association between deprivation and mortality in the study areas. METHODS: We performed principal component analyses of available indicators of the 221 cantons of Ecuador. A set of 41 sociodemographic, social capital, and subjective well-being variables were obtained from the 2010 National Population Census and the National Living Conditions Survey 2013-2014. To explore the application of the index in public health, the association between the index and standardised mortality ratios was estimated through a Poisson regression model. RESULTS: The final index was constructed with 17 indicators. The first component explained 51.8% of the total variance of the data. A geographic pattern and a positive association of the index with the standardised mortality ratios of the cantons were observed in both men and women. CONCLUSIONS: We constructed a deprivation index that can identify disadvantaged areas in Ecuador. This index could be a valuable tool for the detection of vulnerabilised populations and the development of interventions and policies adapted to local needs.